Inducción de embriogénesis somática a partir de embrión cigotico inmaduro de Persea americana Mill.Var. Hass “palto”, utilizando 2,4-diclorofenoxiacético y bencil amino purina. - Polo Sanchez, Maria Aurelia (2017)
Persea americana Mill "avocado"; Is a dicotyledonous, important in gastronomy, aesthetics, nutrition and medicine. At present, it is propagated by conventional methods employing grafts in nurse pattern, which requires considerable space if it is intended to obtain a large production; Which is why the interest of using in vitro techniques such as somatic embryogenesis; To obtain a large scale production of desired genotypes using places that are not very spacious and thus benefit the micro and macro enterprises dedicated to the production of this fruit. In the present work was made with the aim of being able to demonstrate the induction of somatic embryogenesis from immature citotic embryo of "palto"; Whose treatments were: I: 2,4-D / BAP (0.1 / 0 ppm); II: 2,4-D / BAP (0.1 / 1 ppm); III: 2,4-D / BAP (0/1 ppm); IV: 2,4-D / BAP (0.15 ppm); V: 2,4-D / BAP (0/5 ppm); VI: 2,4-D / BAP (0.1 / 10 ppm); VII: 2,4-D / BAP (0/10 ppm), each with its three replicates. The evaluation was based on explants with callus and continuous until the 60 days in which the embryo was obtained, taking as data the gain in weight , Length and the number of embryos per treatment. It was found that only treatments (V and VII) were the only ones that obtained embryos, with a total of (84 and 78) per treatment, both being almost similar quantities, so that there were no significant differences between them respectively. Consequently, the induction of somatic embryogenesis from the immature cigotic embryo of Persea americana Mill.var. Hass "avocado", using 2,4-dichlorophenoxyacetic and benzylaminopurine, was able to induce somatic embryos in the treatments of (V and VII); Of 5 and 10 ppm BAP at 60 days of evaluation.